2022
DOI: 10.1002/mrd.23640
|View full text |Cite
|
Sign up to set email alerts
|

The role of mtDNA in oocyte quality and embryo development

Abstract: The mitochondrial genome resides in the mitochondria present in nearly all cell types. The porcine (Sus scrofa) mitochondrial genome is circa 16.7 kb in size and exists in the multimeric format in cells. Individual cell types have different numbers of mitochondrial DNA (mtDNA) copy number based on their requirements for ATP produced by oxidative phosphorylation. The oocyte has the largest number of mtDNA of any cell type. During oogenesis, the oocyte sets mtDNA copy number in order that sufficient copies are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 127 publications
(185 reference statements)
2
11
0
Order By: Relevance
“…We have shown that supplemented heterologous mtDNA was detectable in tail samples from piglets and adult tissues (brain, calf muscle and heart), and levels of supplemented heterologous mtDNA varied amongst pigs and tissues but were at consistently low levels [29]. Heteroplasmy causes alterations in OXPHOS activity and mitochondrial ROS levels [22], which, in turn, modulate several signalling pathways, including RIG-I-like receptor (RLR) innate immune signalling [38,41]. Indeed, it has also been proposed that inherited mtDNA SNPs and somatic mutations could influence inflammatory pathways by imparting functional changes in mitochondria [38].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We have shown that supplemented heterologous mtDNA was detectable in tail samples from piglets and adult tissues (brain, calf muscle and heart), and levels of supplemented heterologous mtDNA varied amongst pigs and tissues but were at consistently low levels [29]. Heteroplasmy causes alterations in OXPHOS activity and mitochondrial ROS levels [22], which, in turn, modulate several signalling pathways, including RIG-I-like receptor (RLR) innate immune signalling [38,41]. Indeed, it has also been proposed that inherited mtDNA SNPs and somatic mutations could influence inflammatory pathways by imparting functional changes in mitochondria [38].…”
Section: Discussionmentioning
confidence: 96%
“…These processes could explain the changes in expression in inflammatory response pathway genes in blastocysts [20,28]. Heteroplasmy (in this case the presence of two distinct mitochondrial genomes [22]) following heterologous third-party mtDNA supplementation could be one of the possible causes, especially given that the immune response may recognise this population of mtDNA as 'foreign' rather than 'self' mtDNA [40]. We have shown that supplemented heterologous mtDNA was detectable in tail samples from piglets and adult tissues (brain, calf muscle and heart), and levels of supplemented heterologous mtDNA varied amongst pigs and tissues but were at consistently low levels [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms for follicle growth and oocyte maturation involve the signaling molecules mammalian target of rapamycin (mTOR) and AKT (protein kinase B) as the initiators of these processes [ 109 ]. During the reproductive life span, in broad terms, fertility generally correlates with the residual quantity of oocytes remaining in the ovaries (the ovarian reserve) [ 110 ] although a successful pregnancy also depends on the availability of high-quality oocytes [ 111 ]. Typically, the loss of fertility for women becomes apparent during the fourth decade of life ( Figure 2 ).…”
Section: Physiological/biological Ovarian Aging: Protection Using Mel...mentioning
confidence: 99%
“…The supplementation of oocytes at the time of fertilisation with mtDNA, packaged within mitochondria derived from sister oocytes, has shown to improve the rates of the fertilisation and development of mammalian embryos [ 13 , 14 , 17 , 18 ]. This process adds approximately an extra 800 copies of mtDNA [ 13 ], which represents 0.3% of the fertilisable oocyte’s total mtDNA content (~300,000).…”
Section: Introductionmentioning
confidence: 99%